Tolley's sickness and maternity pay : a comprehensive guide to payroll practice and procedure - Tew, Paul (LexisNexis, 2004)
Explains the relationship between State payment of benefits, contractual maternity and sickness payments and eligibility of workers. This handbook explains the legislation and shows you how the rules and regulations affect you - helping you to find accurate information easily.